2018
DOI: 10.17554/j.issn.2409-5680.2018.04.79
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Study of Diabetic Retinopathy with HbA1c and Microalbuminuria

Abstract: Department of Medicine of our facility. All cases were subjected to complete ocular examination after taking demographic and medical history. Diabetic Retinopathy was graded as per ETDRS categories. Biochemical investigations like serum creatinine, serum urea, urine microalbumin levels, Blood sugar (fasting/post prandial), HbA1c were done. RESULTS: Out of 444 cases, Male to female ratio was 0.88: 1, where majority (54.73%) were aged between 41-60 years. 246 patients who did not suffer from retinopathy were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
4
11
0
Order By: Relevance
“…Patients with uncontrolled diabetes had higher chances of developing DR (66.61%). Similar findings were reported by Garg Petal, 17 Long Metal 19 and Lind Metal. 34 Zhang R et al 18 reported that when fasting plasma glucose exceeded 7.03 mmol/L and HbA1c exceeded 6.4%, the prevalence of DR increased sharply.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients with uncontrolled diabetes had higher chances of developing DR (66.61%). Similar findings were reported by Garg Petal, 17 Long Metal 19 and Lind Metal. 34 Zhang R et al 18 reported that when fasting plasma glucose exceeded 7.03 mmol/L and HbA1c exceeded 6.4%, the prevalence of DR increased sharply.…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Lokesh S et al, 16 majority of the patients (38%) were in the age range 61-70 years. Similar findings were reported by Khalid M et al, 12 Pragati Garg, 17 Zhang R, 18 Long M 19 where majority of the patients were above the age of 50 years.…”
Section: Discussionsupporting
confidence: 88%
“…Fundus examination findings positive for retinopathy were observed in 198 (44.59%) cases. Thus, prevalence of diabetic retinopathy in type II diabetic cases with microalbuminuria as observed in present study was 44.59% [28] .…”
Section: Observation and Resultssupporting
confidence: 65%
“…In the present study, majority of diabetic retinopathy patients had very mild to moderate non-proliferative diabetic retinopathy (58.58%) followed by severe to very severe non-proliferative diabetic retinopathy (29.29%), Only 24 (12.12%) cases had proliferative diabetic retinopathy. In different cross-Sectional studies, prevalence of different grades of retinopathy have been shown to be of similar order with prevalence of lower grades of retinopathy being higher as compared to higher grades or proliferative retinopathy [5,14,15,16,17,28] .…”
Section: Observation and Resultsmentioning
confidence: 99%
See 1 more Smart Citation